Pragmatic and Academic Socialization - Duanduan Li (Studies in Applied Linguistics & TESOL, 2008)
As Leslie’s advisee for seven years in the 1990s, I had the privilege of studying with a master teacher, caring mentor, and brilliant researcher who, over time, also became a cherished friend. Leslie’s compassion, sense of humor, passion for her subject matter as well as for life, and her academic vitality—or charisma—have impressed me more than she will ever know. I am indeed grateful for the foundation she gave me in sociolinguistics and second language (L2) pragmatics. I have never known a professor who could engage her students in such a powerful, enlightening, and entertaining way, as I experienced in the many captivating three-hour doctoral seminars I took with Leslie over the years.